2017
DOI: 10.1051/matecconf/201711507001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the forced convection of magnetic nanofluids

Abstract: Abstract. Experimental study of the magnetic nanofluids forced convection in a constant magnetic field was carried out. Dependence study of the magnetic nanofluid heat transfer coefficient on the effect of a constant magnetic field was made. The effect of a constant magnetic field on the pressure drop during the magnetic nanofluid flow was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They concluded that Nu number increases up to 4.36% and 7.19% under the magnetic field intensity of 415 G and 700 G respectively. Guzei et al [12] also conducted an experimental study on Fe 3 O 4 / Water nanofluid flow in a pipe under the effect of constant magnetic field (0.3 T). It was observed that the increment in average convective heat transfer is 13% and 10% with and without magnetic field effect compared to the used distilled water as the working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that Nu number increases up to 4.36% and 7.19% under the magnetic field intensity of 415 G and 700 G respectively. Guzei et al [12] also conducted an experimental study on Fe 3 O 4 / Water nanofluid flow in a pipe under the effect of constant magnetic field (0.3 T). It was observed that the increment in average convective heat transfer is 13% and 10% with and without magnetic field effect compared to the used distilled water as the working fluid.…”
Section: Introductionmentioning
confidence: 99%